The Effect of Teachers’ Ability To Manage Deeplearning And Digital Utilization On Students’ Learning Motivation at SMP Negeri 2 Airmadidi - Faliyanthi Abudi; Joulanda Altje Meiske Rawis; Elni Jeini Usoh (International Journal of Science and Environment (IJSE), 2026)
This study aims to examine the effect of teachers’ ability to manage deep learning and the utilization of digital tools on students’ learning motivation at SMP Negeri 2 Airmadidi. The study employed a quantitative approach with an associative research design. The population consisted of 606 students, with a sample of 92 students selected through purposive sampling. Data were collected using a Likert-scale questionnaire measuring deep learning, digital utilization, and learning motivation. Data analysis was conducted using descriptive statistics and multiple linear regression with the assistance of SPSS. The results indicate that teachers’ ability to manage deep learning and digital utilization each have a significant effect on students’ learning motivation, both partially and simultaneously. These findings suggest that learning approaches emphasizing deep conceptual understanding, along with effective use of digital technology, can enhance students’ engagement, interest, and motivation. Therefore, it is essential to continuously develop teachers’ competencies in implementing deep learning and utilizing interactive digital media.